Child assistance training: Effects of training on parents’ knowledge in children’s language and numeracy development - Vidya Anindhita; Shally Novita; Puspita Adhi Kusuma Wijayanti; Lutfianya Assyifa Budi Santoso; Ajeng Nuranti Syafitri; Hellen La Batavee; Aurelia Felisha Jerome Tampubolon (University of Merdeka Malang, 2023)
Preschool-age children show rapid development in various aspects of their development, including numeracy and language development. Various and appropriate stimulations are expected to optimize their development. Parents as the closest support system for preschool children have a very significant role, especially in helping children optimize their numeracy and language skills. Parents can play an optimal role if they understand children's numeracy and language development. In this community service program, parents are given training on